2021
DOI: 10.1002/jgh3.12615
|View full text |Cite
|
Sign up to set email alerts
|

The ultrasound‐guided attenuation parameter is useful in quantification of hepatic steatosis in non‐alcoholic fatty liver disease

Abstract: Aim To determine the utility of the ultrasound‐guided attenuation parameter (UGAP) for quantifying hepatic steatosis in non‐alcoholic fatty liver disease (NAFLD). Methods Subjects were 84 patients with NAFLD (53 men, 31 women; mean age 54 [20–81] years) who underwent liver biopsy and ultrasonography using a GE LOGIQ E9 system and C1‐6 probe at our hospital between 2017 and 2020. B‐Mode imaging of segment V in the liver was acquired and echo attenuation was assessed using UGAP. Steatosis score (S0: <5%; S1: 5%–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, with the progression of fibrosis, AC values were found to be decreasing. The results from this study were limited by its small sample size [18].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, with the progression of fibrosis, AC values were found to be decreasing. The results from this study were limited by its small sample size [18].…”
Section: Discussionmentioning
confidence: 83%
“…The difference in which the steatotic and normal liver attenuates acoustic waves is how the AC measures are quantified [28]. Ogino et al found a positive correlation r = 0.81, P < 0.01 between the AC values and LFC% (liver fat content%), and also good diagnostic accuracy scores for steatosis [18]. Nevertheless, with the progression of fibrosis, AC values were found to be decreasing.…”
Section: Discussionmentioning
confidence: 99%
“…Six published studies compared the UGAP-determined AC values with the reference methods in the assessment of steatosis grades, in which the authors established cut-off values that seemed similar to those obtained via ATI [ 72 , 80 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Quantitative Ultrasound-based Methodsmentioning
confidence: 99%
“…Ogino et al compared the AC obtained using the UGAP with the steatosis grades from liver specimens in 84 patients with NAFLD, and found a significant difference in the AC values among the different grades ( p < 0.01), as well as an increase in AC values with the steatosis score. The liver fat content determined via a pathohistological evaluation of an LB specimen showed a positive correlation with the AC (r = 0.81, p < 0.01), with cut-off values and AUROCs for S1, S2 and S3 of 0.6 (AUROC 0.94), 0.71 (AUROC 0.95) and 0.72 (AUROC 0.88) dB/cm/MHz, respectively [ 83 ].…”
Section: Quantitative Ultrasound-based Methodsmentioning
confidence: 99%
“…Studies have shown that the ultrasound attenuation imaging (ATI) with a convex array is an accurate diagnostic method for tissue changes in liver, especially steatosis [4][5][6][7][8], but the same technique has yet to be fully explored using a linear probe. Attenuation imaging has been used by Canon in the Aplio series of devices to determining the attenuation coefficient in the assessment of non-alcoholic fatty liver disease [9][10][11].…”
Section: Introductionmentioning
confidence: 99%